H.I.D.R.A.: A Hierarchical, Interactive and Dynamic Recognition Architecture for Product Categorization - Ferreira, Renato Cordeiro; Bonadio, Ígor; Resende, Vinicius; Marouelli, Beatriz; Koch, Junior; Oliveira, Henrique; Fadelli, Leandro; Alponti, Helton; Formento, André; Vedovato, Rodrigo (Anais Estendidos do Congresso Brasileiro de Software: Teoria e Prática (CBSoft); 2020: Anais Estendidos do XI Congresso Brasileiro de Software: Teoria e Prática, 2020)
The Hierarchical, Interactive and Dynamic Recognition Architecture (H.I.D.R.A.) for Product Categorization is a new intelligent system architecture developed by Elo7 to easily evolve its category tree and automatically classify millions of products, thus improving the page ranking of our marketplace.